Throat Swab Culture Positivity and Antibiotic Resistance Profiles in Children 2–5 Years of Age Suspected of Bacterial Tonsillitis at Hargeisa Group of Hospitals, Somaliland: A Cross-Sectional Study - Darod, Hamda Hussein; Melese, Addisu; Kibret, Mulugeta; Mulu, Wondemagegn (International Journal of Microbiology, 2023)
Introduction. Tonsillitis is the third most frequently diagnosed infection in the pediatric age and is associated with significant morbidity and loss of school attendance. Throat swab cultures are useful for the confirmation of children with a clinically suspected tonsillitis. However, Somaliland is one of the underdeveloped countries with a low standard of sanitation and poor health seeking culture. Treatment of tonsillitis with antibiotics is irrational and not empirical. This study determined the bacterial throat swab culture positivity and antibiotic resistance profiles of the bacterial isolates among children 2–5 years of age with suspicion of tonsillitis at Hargeisa Group of Hospital, Somaliland. Materials and Methods. A cross-sectional study was conducted from March to July 2020. A total of 374 children from 2 to 5 years of age suspicion of tonsillitis was included using a convenient sampling method. Throat swabs were collected, and bacterial isolation and identification were done using standard bacteriological procedures. Antimicrobial susceptibility testing was done using the disk diffusion method. Data on demographic variables and clinical profiles were collected using structured questionnaires. Logistic regression analysis was computed to identify factors associated with bacterial tonsillitis. Results. Overall, 120 (32.1%) (95% CI 27.4–36.8%) of children were positive for bacterial throat cultures. Of these, 23 (19.2%) were mixed bacterial isolates. The most frequent bacterial isolates were beta-hemolytic streptococci 78 (55%), Staphylococcus aureus 42 (29%), and Streptococcus pneumoniae 10 (7%). Isolates revealed 83.3–100% rate of resistance to ampicillin. Beta-hemolytic streptococci isolates were 94.9% resistant to ampicillin. S. aureus was resistant to clarithromycin (38%) while S. pneumoniae isolates were 100% resistant to ampicillin. History of tonsillitis (AOR = 0.12; 95% CI = 0.06–0.21), difficulty in swallowing (AOR = 6.99; 95% CI = 3.56–13.73), and attending schools (AOR = 2.98; 95% CI = 1.64–5.42) were found to be associated with positive throat culture. Conclusions. Resistance to ampicillin and MDR among beta-hemolytic streptococci and other isolates of throat colonizers in children with clinically suspected of bacterial tonsillitis are major concerns in Hargeisa, Somaliland. Therefore, treatments of cases are recommended to be guided by regular culture and antimicrobial susceptibility testing to prevent complications of tonsillitis and associated antibiotic resistance.